Approximation in variation for Mellin integral operators. Issue 1 (21st October 2015) - Angeloni, Laura; Vinti, Gianluca
Abstract We study approximation results for a family of Mellin integral operators in the space of functions of bounded variation in the multidimensional setting, by means of a new concept of variation for multivariate functions. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)